Biomechanical comparative analysis of temporomandibular joint, glenoid fossa and head of the condyle of conventional models prothesis with new PEEK design - Wladimir Genovesi; Iara Cristina Comenale; Wladimir Genovesi Filho; Moises Veloso Fernandes (Journal of Oral Biology and Craniofacial Research)
This article reviews the design of the temporomandibular joint (TMJ) prostheses used for TMJ joint replacement from 2000 to 2020. The TMJ is a complex joint, with distinct anatomical and functional characteristics making it challenging to maintain. Many authors from the early 20th century reported techniques for TMJ reconstruction, with the goal of restoring its shape and ideal function. Many prototypes have been developed in pursuit of an ideal prosthesis that adheres to the principles of biomechanics and biocompatibility, with good long-term performance and lower cost.The TMJ prosthesis is divided in two parts: the glenoid fossa and the mandibular ramus component.These two parts are fixed with metal screws in the glenoid fossa and fixed in the zygomatic arch with 4 or 5 screws. The mandibular part is fixed to the mandible ramus with 8 or 9 titanium screws.In our review, since 2000 to 2020, little has changed to improve the design and allow for natural mandible movement. From 2000 to 2006, 48 TMJ surgeries were performed using UHMWPE with this design. All patients had good results, preserving opening mouth and lateral movements.All the designs are similar in principle. The glenoid fossa, which resembles a box, limiting the rotation and translation movement. It is known that lateral movements are lost in function as the lateral pterygoid muscle is detached.